Potent Anti-SARS-CoV-2 Activity by the Natural Product Gallinamide A and Analogues via Inhibition of Cathepsin L - Ashhurst, Anneliese S; Tang, Arthur H; Fajtová, Pavla; Yoon, Michael C; Aggarwal, Anupriya; Bedding, Max J; Stoye, Alexander; Beretta, Laura; Pwee, Dustin; Drelich, Aleksandra; Skinner, Danielle; Li, Linfeng; et al. (Journal of medicinal chemistry, 2022)
Cathepsin L is a key host cysteine protease utilized by coronaviruses for cell entry and is a promising drug target for novel antivirals against SARS-CoV-2. The marine natural product gallinamide A and several synthetic analogues were identified as potent inhibitors of cathepsin L with IC50 values in the picomolar range. Lead molecules possessed selectivity over other cathepsins and alternative host proteases involved in viral entry. Gallinamide A directly interacted with cathepsin L in cells and, together with two lead analogues, potently inhibited SARS-CoV-2 infection in vitro, with EC50 values in the nanomolar range. Reduced antiviral activity was observed in cells overexpressing transmembrane protease, serine 2 (TMPRSS2); however, a synergistic improvement in antiviral activity was achieved when combined with a TMPRSS2 inhibitor. These data highlight the potential of cathepsin L as a COVID-19 drug target as well as the likely need to inhibit multiple routes of viral entry to achieve efficacy.
Keywords: Animals; Antiviral Agents; biologické přípravky; Chlorocebus aethiops; molekulární konformace; vztah mezi dávkou a účinkem léčiva; Cathepsin L; SARS-CoV-2; mikrobiální testy citlivosti; Biological Products; antivirové látky; farmakoterapie COVID-19; Vero Cells; kationické antimikrobiální peptidy; Structure-Activity Relationship; lidé; proteomika; Vero buňky; A549 Cells; COVID-19; Molecular Conformation; Proteomics; Microbial Sensitivity Tests; Cysteine Proteinase Inhibitors; Dose-Response Relationship, Drug; kathepsin L; COVID-19 Drug Treatment; vztahy mezi strukturou a aktivitou; Cercopithecus aethiops; Antimicrobial Cationic Peptides; zvířata; inhibitory cysteinových proteinas; buňky A549; Humans